The Classification of The Quranic Suras - Part One: Structural Analysis and Organization into Groups Generated by Sura Al-F?ti?ah - Benzitouni, Saadane (Journal of Quranic Sciences and Research, 2025)
This study aims to assess, using a rigorous scientific approach, whether the current ordering of the Quranic suras results from an intentional and predetermined organization or from a random arrangement. The methodology is based on discovery of a fundamental mathematical property, Equation 1 , which establishes a unique functional relationship between the sum of the sura numbers (N), the total number of verses (V), and the sum of the verse numbers (SV) of the Noble Quran. The analysis used the sign of the ranking value D(a), derived from Equation (1), as a criterion to distribute the surahs into major structural groups (TA, TB, BZ), thereby revealing a coherent underlying architecture. This research has brought to light remarkable structural properties governing these groups and their subdivisions (BZ?, BZ?, IZ?, IZ?), including a series of equilibrium equations such as and . The study further demonstrates the central functional role of specific suras, such as Sura Al-F?ti?ah, acting as a regulatory pivot. The mathematically verifiable, interdependent complexity and coherence of this architecture constitute strong evidence of a non-random design. A complementary part of this research, dedicated to the analysis of other partitions, will further consolidate this model. The ultimate objective is to demonstrate that the Quran adheres to a coherent and sophisticated internal mathematical organization, thereby confirming the validity and relevance of its current canonical order.